42nd AIAA Fluid Dynamics Conference and Exhibit 2012
DOI: 10.2514/6.2012-3151
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations of Local Correlation-Based Transition Model in Hypersonic Flows

Abstract: Numerical simulations of hypersonic flows using local correlation based transition (LCTM) model was performed in order to assess the accuracy of the model in hypersonic conditions. Implementation of the model was done in object oriented framework. The governing equations as well as the numerical methods are described. A series of runs were performed for simulating Mach 8 flow over a 7 o half angle sharp cone, using three different free stream turbulence intensity levels. Moreover, both Laminar and fully turbul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Krause, Behr and Ballmann [18] constructed a relationship between F length and Re θ c by considering freestream turbulence intensities, allowing the simulation results to agree well with the experimental data in the cases of hypersonic double ramp. Bensassi, Lani and Rambaud [19] tested the model by simulating a Mach 8 flow over a 7 • half angle sharp cone at three different freestream turbulence intensity levels, where they reported that the heat flux in the transition regime shows excellent agreement with experimental data. Zhang et al [20,21] calibrated the basic γ − Re θ empirical correlation with different samples and results in different cases are satisfactory.…”
Section: Introductionmentioning
confidence: 98%
“…Krause, Behr and Ballmann [18] constructed a relationship between F length and Re θ c by considering freestream turbulence intensities, allowing the simulation results to agree well with the experimental data in the cases of hypersonic double ramp. Bensassi, Lani and Rambaud [19] tested the model by simulating a Mach 8 flow over a 7 • half angle sharp cone at three different freestream turbulence intensity levels, where they reported that the heat flux in the transition regime shows excellent agreement with experimental data. Zhang et al [20,21] calibrated the basic γ − Re θ empirical correlation with different samples and results in different cases are satisfactory.…”
Section: Introductionmentioning
confidence: 98%
“…Krause and Behr [18] constructed a relationship between F length and Re θc by considering freestream turbulence intensities, allowing the simulation results to agree well with the experimental data in the cases of hypersonic double ramp. Bensassi, Lani and Rambaud [19] tested the model by simulating a Mach 8 flow over a 7 • half angle sharp cone at three different freestream turbulence intensity levels, where they reported that the heat flux in the transition regime shows excellent agreement with experimental data. Zhang et al [20,21] calibrated the basic γ − Re θ empirical correlation with different samples and results in different cases are satisfactory.…”
Section: Introductionmentioning
confidence: 98%